If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -6x = -20 Solving -2 + -6x = -20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -6x = -20 + 2 Combine like terms: -2 + 2 = 0 0 + -6x = -20 + 2 -6x = -20 + 2 Combine like terms: -20 + 2 = -18 -6x = -18 Divide each side by '-6'. x = 3 Simplifying x = 3
| 3x(144)+12=29 | | -16t^2+26t+12= | | -4x+18=9 | | 6(y+3)=42 | | 3x+103=7x-3 | | y+7=-(x+5) | | 9x+6=12x+18 | | 13=n-5 | | 2x+30=63 | | x+0.78=15 | | -3y-4=-2y-7 | | 4x-3(x-1)=6 | | Y=6sinc | | r^2+24+144=0 | | 6x+10=5x+93 | | 2p+4b=350 | | 2.4y=19.44 | | 170=25x+30x | | 4(3x+9)=-28+40 | | 2x+1=-7x+154 | | 2/7-6/x= | | 3(w+2)=2+2w | | 6x+-3=33+3x | | 8-(2y-8)=9-3y | | Logx-2=0 | | 4Z+27=30+2Z | | 8-(2n-2)=4-3n | | X=0.75x+5 | | ln(9y)= | | b/2=2 | | 6(4+6)=5(c-2) | | 7Y+12-5Y=42 |